The effectiveness of mindfulness-based stress reduction (MBSR) on depression, PTSD, and mindfulness among military veterans: A systematic review and meta-analysis - Wendy Wen Li; Jaime Nannestad; Timothy Leow; Carolyn Heward (Health Psychology Open)
Thirteen studies were included in the current systematic review and meta-analysis with 1131 participants. Both within- and between-group comparisons demonstrated reductions in depressive and PTSD symptoms with medium effect sizes post MBSR intervention. Additionally, MBSR demonstrated small effects in improving mindfulness in veterans at post-intervention. Maintenance of treatment effects were observed at follow-up for the three outcomes during within-group comparisons. Treatment effects were maintained at follow-up between-groups for depression and mindfulness, but not for PTSD symptoms. Furthermore, there were no significant differences between MBSR and cognitive behavioural therapy/person-centred group therapy intervention groups in the three outcomes.